2021
DOI: 10.21608/mid.2021.85894.1170
|View full text |Cite
|
Sign up to set email alerts
|

Detection of virulence genes (magA and rmpA) and resistance gene (CTX-M) in Klebsiella pneumoniae isolated from neonates with septicemia

Abstract: Background: Neonatal sepsis (NS) due to K. pneumoniae is a major cause of morbidity and mortality in neonates. This study aimed to study the risk factors of NS caused by K.pneumoniae in NICU in Menoufia University Hospitals and to detect rmpA and magA virulence genes and CTX-M antibiotic resistance gene. Correlation between compliance of infection control measures and occurrence of NS and its outcome were also evaluated. Methods: Klebsiella pneumoniae were isolated from blood of neonates with sepsis and studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The results indicated a significantly higher level of blaCTX-M-15 gene expression in K. pneumoniae isolates (KR1-KR23) compared to susceptible isolates (p < 0.01). The findings were supported by Ghonaim et al (2021), who reported a significant difference in the presence of the CTX-M gene between ESβL-producing and non-ESβL-producing K. pneumoniae isolates. Calibration curves for each gene were produced using serially diluted cDNA prepared from in vitro-obtained RNA standards.…”
Section: Discussionmentioning
confidence: 52%
“…The results indicated a significantly higher level of blaCTX-M-15 gene expression in K. pneumoniae isolates (KR1-KR23) compared to susceptible isolates (p < 0.01). The findings were supported by Ghonaim et al (2021), who reported a significant difference in the presence of the CTX-M gene between ESβL-producing and non-ESβL-producing K. pneumoniae isolates. Calibration curves for each gene were produced using serially diluted cDNA prepared from in vitro-obtained RNA standards.…”
Section: Discussionmentioning
confidence: 52%
“…In our study, strains of hvKp showed more resistance to antibiotics than cKP although this difference was not significant. Different results were stated by Ghonaim et al 24 they reported that the resistance rate in hvKp was lower than cKp as hvKps do not take up DNA from other resistant bacteria due to an increase expression of capsule-related genes large capsule size 25 .…”
Section: Discussionmentioning
confidence: 68%
“…For the genotypic characterization of hmvKp, 25 isolates out of 30 (83.3%) were rmpA gene positive. Similarly, Guo et al 29 , Ghonaim et al 24 showed that 12 out of 14 (85.7%), 17 out of 19 (89.5%) hmvKp strains carried rmpA gene respectively. Moreover, Lin et al 30 showed that 100 out of 124 (80.65%) of strains of hvKp harbored rmpA gene.…”
Section: Discussionmentioning
confidence: 81%